Attitudes towards AI counseling: the existence of perceptual fear in affecting perceived chatbot support quality - Keung, Wing Man; So, Tsz Yan (Frontiers in Psychology, 2025)
IntroductionDue to the shortage of financial and human resources in the local mental health industry, AI counseling presents itself as a cost-effective solution to address this limitation. However, fear and concerns about AI may hinder the adoption of AI in counseling. This study examined the relationships between individuals’ prior AI exposures, AI anxiety levels, attitudes towards AI, and their perceived support satisfaction with the counseling chatbot.MethodsWith a simulated counseling chatbot developed using Azure OpenAI GPT-4 model (1106-preview version) and a sample of 110 local Chinese in Hong Kong, this study explored the potential existence of perceptual fear in affecting people’s perceived support quality of the chatbot by manipulating the informed perceptual labels—Told-Human (told to be receiving human counseling) and Told-AI (told to be receiving AI counseling).ResultsPerceptual fear of AI adversely affected participants’ perceived support quality of the counseling chatbot, t (108) = 2.64, p = 0.009, BCa 95% CI = [0.186, 1.342], with Hedges’ correction of 1.55. While the significant reduction in stress levels demonstrated the chatbot’s implicit capability in providing emotional support (p = 0.03), participants showed explicit reservations about its helpfulness.DiscussionThis study highlights the importance of accounting for the influence of individuals’ pre-existing beliefs on the perceived support quality of counseling chatbots. Future cross-cultural studies with a larger sample may shed more light by investigating dynamic intervention approaches and conducting sentiment and thematic analyses of client-chatbot conversations.